Pharyngeal Reconstruction with Microvascular Free Tissue Transfer - Sokoya, Mofiyinfolu; Bahrami, Arash; Vincent, Aurora; Inman, Jared; Mourad, Moustafa; Sawhney, Raja; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
Reconstruction of pharyngoesophageal defects after total laryngectomies and extirpation of hypopharyngeal and upper esophageal carcinomas presents a challenging task. Goals of reconstruction include adequate voice rehabilitation and restoration of normal swallowing. The reconstructive armamentarium contains many options for reconstruction and creation of a new upper digestive tract. This review article focuses on the most commonly used free tissue transfer options for the reconstruction of these defects, with an assessment of their advantages and disadvantages.
Keywords: pharyngeal reconstruction; free flaps; neck; reconstruction